Concise encyclopedia of Amish, Brethren, Hutterites, and Mennonites - Kraybill, Donald B. (Johns Hopkins University Press, 2010)
Donald B. Kraybill has spent his career among Anabaptist groups, gaining an unparalleled understanding of these traditionally private people. Kraybill shares that deep knowledge in this succinct overview of the beliefs and cultural practices of Amish, Brethren, Hutterites, and Mennonites in North America. Found throughout Canada, Central America, Mexico, and the United States, these religious communities include more than 200 different groups with 800,000 members in 17 countries. Through 340 short entries, Kraybill offers readers information on a wide range of topics related to religious views and social practices. With thoughtful consideration of how the diverse communities are related, this compact reference provides a brief and accurate synopsis of these groups in the twenty-first century. No other single volume provides such a broad overview of Amish, Brethren, Huterites, and Mennonites in North America. Organized for ease of searching--with a list of entries, a topic finder, an index of names, and ample cross-references--the volume also includes abundant resources for accessing additional information. Wide in scope, succinct in content, with directional markers along the way, the Concise Encyclopedia of Amish, Brethren, Hutterites, and Mennonites is a must-have reference for anyone interested in Anabaptist groups.--Book Jacket.